The importance of the occipitocervical area in patients with ankylosing spondylitis analysis of a cohort of 86 cervical fractures in surgically treated patients - Augusto Atilio Covaro; Nodoka Manabe; Lukas Bobinski; Claes Olerud; Yohan Robinson (Journal of Craniovertebral Junction and Spine, 2017)
Study Design: This was a retrospective analysis of prospectively collected data. Objective: The effect of C0-C1-C2 cervical ankylosis in patients with ankylosing spondylitis (AS) is not documented. The objective of this study is to describe the radiological characteristics of the occipitocervical junction in patients with AS operated for a cervical fracture and to correlate them with their clinical evolution. Materials and Methods: Analysis of patients with ankylosing spondylitis (AS) treated in a single institution of a cervical vertebral fracture between 2007 and 2014 who were prospectively followed through the SWESPINE registry. The integrity of the C0–C1–C2 joints was determined and classified into fused and nonfused joints. By determining the angle between C0–C1 and C1–C2 joints in the coronal view of the computed tomography scan (X-angle), the progressive degeneration of these joints was described. Intra- and inter-observer reliability of this test was determined. The instruments of health-related quality of life (QOL) and disability were EQ5D and Oswestry disability index (ODI), respectively. Results: A total of 86 patients with AS treated surgically for cervical fracture had complete facet ankylosis between C3 and T1 due to their pathology. Mean age 69.2 years (standard deviation [SD]: 11.7). The most common level of fracture was in C5–C6. In 24 patients, the C0–C1 joint was fused, and in 15 patients, C1–C2 joint was fused. The intra- and inter-class reliabilities for X-angle measurement were very high (intraclass correlation coefficients = 0.94; 0.92). The mean X-angle was 125° (SD: 12) in nonfused patients and 136° (SD: 14) in fused patients (P < 0.001). There were no differences in QOL and disability at 2 years between the two groups: EQ5D-index of 0.54 and 0.55 (P = 0.5), ODI of 26.4 and 24, (P = 0.35) respectively. Conclusions: X-angle is a reliable measure for joint integrity C0–C1–C2 in patients with AS. Total cervical ankylosis including the C0-C1-C2 segments is not related to poorer QOL and disability in these patients.